214. PRE-EXISTING MESH AT THE HIATUS INCREASES MORBIDITY DURING AND AFTER REVISIONAL ANTIREFLUX SURGERY: A NATIONAL COHORT STUDY. (24th September 2022) - Liu, David; Goh, Su Kah; Wong, Darren; Stevens, Sean; Aly, Ahmad; Bright, Tim; Watson, David; ,
Abstract: Revisional antireflux surgery including hiatus hernia repair is increasingly common. Mesh augmented hiatal closure at the time of index operation is controversial but commonly performed. Whilst metanalysis of randomized data has demonstrated no additional benefit of routine mesh placement, it is unclear whether this practice results in harm, particularly at the time of revisional antireflux surgery. In this study, we determined whether pre-existing mesh at the hiatus increases morbidity during and after revisional antireflux surgery. Analysis of prospectively-maintained databases and medical records of all elective revisional antireflux surgery cases in 36 hospitals across Australia over 10 years. The outcomes of patients with and without pre-existing mesh at the hiatus were compared. Study endpoints included intraoperative adverse events (bleeding, unplanned oesophago-gastric resection, open conversion, and injury to liver, pleura, oesophagus, stomach, spleen, lung, heart, major venous and arterial structures) and postoperative complications (defined by the Esophagectomy Complication Consensus Guidelines). Propensity score matched analysis was used to validated primary findings. 346 revisional cases (35 with pre-existing mesh) were analyzed. The two groups had comparable baseline characteristics. In total, 77 (22.2%) patients had 148 intraoperative adverse events. Pre-existing mesh was associated with a higher risk of intraoperative adverse events (48.6% versus 22.5%, OR 3.25, 95% CI 1.63–6.38, p = 0.002), secondary to bleeding, and injury to pleura, lung, and liver. Overall, 63 (18.2%) patients developed postoperative complications. Pre-existing mesh was associated with increased postoperative morbidity (37.1% versus 16.1%, OR 3.09, 95% CI 1.50–6.43, p = 0.005), particularly due to bleeding and respiratory complications. Importantly, pre-existing mesh independently predicted the occurrence of intraoperative and postoperative complications. Pre-existing mesh at the hiatus significantly increases morbidity during and after revisional antireflux surgery. Given that revisional surgery is increasingly being performed, our findings further discourage the use of mesh around the hiatus during antireflux surgery.